La comunidad política como espacio ético-teológico: reinterpretación hermenéutica de la Doctrina Social de la Iglesia en el Perú contemporáneo - Pérez Momba, Wualdo Vicente (2026)
This article analyzes the crisis of the political community in contemporary Peru, understood as both an institutional problem and an ethical, social, and cultural fracture that affects the meaning of living together. The objective of this study, grounded in a hermeneutical-theological approach, is to reinterpret the political community in light of the Social Doctrine of the Church, in dialogue with Latin American theology and the Peruvian context. The analysis shows that structural corruption, social fragmentation, and the exclusion of the most vulnerable sectors reveal the loss of the common good as the guiding horizon of politics. In response, it is proposed that the political community can be understood as an ethical-theological space where human dignity, justice, and shared responsibility are articulated. Likewise, the centrality of the people as a historical subject and the preferential option for the poor are highlighted as key criteria for evaluating the legitimacy of political life. The article concludes that rethinking politics from this perspective opens possibilities for its reconstruction in terms of service, fraternity, charity, and social transformation.